Comparative Analysis of Flexural Strength and Reinforcement Weight of Flat Slab Floor System and Beam-Slab Floor System - Joseph, Joseph; Nasruddin Nasruddin; Hartawan Hartawan (International Journal of Computational and Experimental Science and Engineering, 2025)
Analysis of reinforcement efficiency in concrete floor slab systems is a critical aspect of architectural and structural design, requiring significant time and precision. Advances in software have revolutionized this process by enabling accurate modeling, simulation, structural analysis, design, and optimization in a shorter timeframe. This study focuses on a comparative analysis of flexural strength and reinforcement weight between Flat Slab and Plate Beam floor systems. The research employs Safe v.21 software to model, simulate, and analyze these systems. The study uses varying non-fixed variables (such as frame specification and volume) while maintaining consistent fixed variables (material specifications, load cases, load combinations, and other structural parameters). The findings indicate distinct differences in performance metrics, including displacements, beam moments, shear forces, axial forces, and shell stress. The results demonstrate that the Flat Slab system offers greater reinforcement efficiency. The novelty of this research lies in the application of Safe v.21 software, which provides enhanced accuracy in evaluating the flexural strength and reinforcement characteristics of concrete floor slabs.